2011
DOI: 10.1103/physrevb.83.094112
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the iron oxides and oxyhydroxides for the prediction of environmentally sensitive phase transformations

Abstract: Iron oxides and oxyhydroxides are challenging to model computationally as competing phases may differ in formation energies by only several kJ mol −1 , they undergo magnetization transitions with temperature, their structures may contain partially occupied sites or long-range ordering of vacancies, and some loose structures require proper description of weak interactions such as hydrogen bonding and dispersive forces. If structures and transformations are to be reliably predicted under different chemical condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 106 publications
(165 reference statements)
4
83
0
Order By: Relevance
“…where Dl 0 (T r ) is the connection energy at standard pressure (1 atm) and temperature (300 K), and C p is the molar heat capacity (Guo and Barnard, 2011). As reported in Table 2, the results of these calculations showed that the relative stabilities of Al-goethites were not affected by temperature corrections.…”
Section: Energiesmentioning
confidence: 87%
See 1 more Smart Citation
“…where Dl 0 (T r ) is the connection energy at standard pressure (1 atm) and temperature (300 K), and C p is the molar heat capacity (Guo and Barnard, 2011). As reported in Table 2, the results of these calculations showed that the relative stabilities of Al-goethites were not affected by temperature corrections.…”
Section: Energiesmentioning
confidence: 87%
“…The difference for the six Al case is even greater, so the ZPE approximation would have an even smaller effect for these models. Lastly, we tested the effect temperature differences might have on the relative energies of our systems (third assumption) by comparison of DTOTEN VASP rxn (at 0 K) and connection energy at standard state conditions (Guo and Barnard, 2011). The connection energy, which represents energy variations between TOTEN at 0 K and at standard state, was calculated by:…”
Section: Energiesmentioning
confidence: 99%
“…Experimental studies encounter difficulties of reproducibility in controlling environmental conditions and characterizing hydrated surfaces [17][18][19]. Computational modeling is confronted with strongly-correlated electronic structures of hematite (and other iron oxides) [20][21][22] and an enormous number of possible surface hydroxylation configurations [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Substitution energies were calculated for each mode at the vertices of the polygon (points A to E, which run from maximum oxidizing to maximum reducing conditions) for three different iron environments: FeO (case 1), α-Fe 2 O 3 (case 2) and bcc bulk Fe (case 3). Table 2 compares the values for the cohesive energies, lattice parameters, energy gaps and magnetic moment per site calculated in this work with those taken from the literature [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] -no data were found for the gaps of tetragonal BaO 2 and TiO. In the context of this work, these data are relevant, since the defect energies are defined in terms of the respective chemical potentials, which depend on the cohesive energies.…”
Section: Defect Energies Calculationmentioning
confidence: 99%